2016
DOI: 10.1007/s40265-016-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Amphotericin B (AmBisome®): A Review of the Pharmacokinetics, Pharmacodynamics, Clinical Experience and Future Directions

Abstract: Liposomal amphotericin B (AmBisome®; LAmB) is a unique lipid formulation of amphotericin B. LAmB is a standard of care for a wide range of medically important opportunistic fungal pathogens. LAmB has a significantly improved toxicity profile compared with conventional amphotericin B deoxycholate (DAmB). Despite nearly 20 years of clinical use, the pharmacokinetics and pharmacodynamics of this agent, which differ considerably from DAmB, remain relatively poorly understood and underutilized in the clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
272
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(285 citation statements)
references
References 117 publications
(153 reference statements)
4
272
0
9
Order By: Relevance
“…Recent clinical studies have suggested limited benefits and higher risk of nephrotoxicity with increasing daily doses of L-AMB in the treatment of cryptococcal meningitis (17), invasive aspergillosis (18), and possibly mucormycosis (19). However, novel dosing approaches using a combination of high induction doses followed by lower maintenance doses are under investigation for cryptococcosis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have suggested limited benefits and higher risk of nephrotoxicity with increasing daily doses of L-AMB in the treatment of cryptococcal meningitis (17), invasive aspergillosis (18), and possibly mucormycosis (19). However, novel dosing approaches using a combination of high induction doses followed by lower maintenance doses are under investigation for cryptococcosis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Since Fungizone, the micellar formulation of AMB, quickly releases its payload following administration, it causes severe toxic adverse effects, including acute infusion-related toxicities and chronic nephrotoxicity, which limit its clinical use (14). Three different lipid-based nanoformulations of AMB (Amphotec, Abelcet, and AmBisome) have been developed and commercialized in the United States and Europe in order to increase tolerance and the therapeutic index of AMB and to reduce drugrelated adverse effects (15). Liposomal AMB is widely used in the treatment of VL (11).…”
Section: Discussionmentioning
confidence: 99%
“…in catheters; and continued understanding of pharmacokinetics/pharmacodynamics, of pediatric usage, and of mechanism of action. See Stone et al (2016).…”
Section: Future Directionsmentioning
confidence: 99%